The rise of the supermax in Brazil - De Jesus Filho, José [UNESP] (My University, 2012)
IN 1985, the state government of São Paulo created a separate annex to a psychiatric penitentiary hospital, establishing the Penitentiary Rehabilitation Center of Taubaté, commonly called the Piranhão, for the incarceration of the most violent inmates of the state. Before its creation, the only previous disciplinary penitentiary to house high-risk inmates had been located on Anchieta Island, off the São Paulo coast, which was closed in 1952 after a bloody mass escape. The reasons for placing inmates in Taubaté ranged from locking down escape-prone and disruptive inmates to deterring inmatestaff violence, murders, and active participation in riots. Other undefined notions, such as the labeling of some inmates as highly dangerous, served as further justifications for the regimen pursued at the Rehabilitation Center (Teixeira 2009).